ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH PADA LIRIK LAGU RUMAH SINGGAH KARYA FABIO ASHER - Aulia Putri, Rizqi; Sholikhati, Nur Indah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to analyze the representation of unequal emotional relationships in the lyrics of Fabio Asher’s song “Rumah Singgah” using Norman Fairclough’s critical discourse analysis approach. The scope of this study focuses on revealing the meaning of one-sided love, emotional sacrifice, and unequal reliationships constructed through language in song lyrics. The method used is descriptive qualitative, applying Fairclough’s three dimensions of analysis, namely text, discourse practice, and sociocultural practice. The research data consists of the lyrics of the song “Rumah Singgah” and listener responses obtained from comment columns on digital platforms such as YouTube and TikTok. The results of the study show that the song lyrics represent the subject “i” as the party who acts as an emotional support without receiving equal recognition and commitment. The metaphor “rumah singgah” (temporary shelter) is the core of the discourse that affirms the subject’s position as a temporary refuge, not the ultimate goal in a relationship.